The Main Trends in the XX Century Economics’ Methodology - Martišius, Stanislovas Algimantas (Ekonomika, 2003)
The main idea of the article is to disjoin empiricism and rationalism, or apriority, and it is made evident when investigating the streams of the XX century economic thought It is stressed the exceptional feature of the current economics, hypothesizing, which became the main instrument in the building of a new theoretical constructions.If to choose from a few alternatives when creating a new economic theory, the preference must be given to the one, where more empirical information is used, the logic of the facts prefer, the better elucidatory and predictive possibilities as well as faster verification, when compare observations and based on the theory outcomes.A following general conclusions when investigating the XX century economics’ methodology could be presented:1. Current economic hypotheses couldn’t be based solely on the induction or deduction.2. The building of a new economic hypothesis exceeds the bounds of empirical facts, at the same time it suggests the preliminary solution of the problem, or establishes a new law describing economic reality.3. The economics starts from the problem, not from the observations, although the economic problem could be raised on the reliable observations.